Provision of Small-Quantity Lipid-Based Nutrient Supplements Increases Plasma Selenium Concentration in Pregnant Women in Malawi: A Secondary Outcome of a Randomized Controlled Trial. Issue 3 (7th March 2022) - Haskell, Marjorie J; Maleta, Kenneth; Arnold, Charles D; Jorgensen, Josh M; Fan, Yue-Mei; Ashorn, Ulla; Matchado, Andrew; Monangi, Nagendra K; Zhang, Ge; Xu, Huan; Belling, Elizabeth; Landero, Julio; et al.
ABSTRACT: Background: Pregnant women in Malawi are at risk of selenium deficiency, which can have adverse effects on pregnancy outcomes. Interventions for improving selenium status are needed. Objectives: To assess the effect of provision of small-quantity lipid-based nutrient supplements (SQ-LNSs) to Malawian women during pregnancy on their plasma selenium concentrations at 36 wk of gestation. Methods: Pregnant women (≤20 wk of gestation) were randomly assigned to receive daily either: 1 ) iron and folic acid (IFA); 2 ) multiple micronutrients (MMN; 130 µg selenium per capsule); or 3 ) SQ-LNS (130 µg selenium/20 g). Plasma selenium concentrations were measured by inductively coupled plasma mass spectrometry at baseline and after ≥16 wk of intervention (at 36 wk of gestation) and compared by intervention group. Results: At 36 wk of gestation, median (quartile 1, quartile 3) plasma selenium concentrations (micromoles per liter) were 0.96 (0.73, 1.23), 0.94 (0.78, 1.18), and 1.01 (0.85, 1.28) in the IFA, MMN, and SQ-LNS groups, respectively. Geometric mean (GM) plasma selenium concentration was 5.4% (95% CI: 1.8%, 9.0%) higher in the SQ-LNS group than in the MMN group and tended to be higher than in the IFA group (+4.2%; 95% CI: 1.0%, 7.8%). The prevalence of adjusted plasma selenium concentrations <1 µmol/L was 55.1%, 57.8%, and 47.3% in the IFA, MMN, and SQ-LNS groups, respectively; it was lower in the SQ-LNS group than in the MMN group, OR = 0.44 (95% CI: 0.24, 0.83), and tended to be lower than in the IFA group, OR = 0.54 (95% CI: 0.29, 1.03). There was a significant interaction between baseline plasma selenium concentration and intervention group ( P  = 0.003). In the lowest tertile of baseline selenium concentrations, GM plasma selenium concentration was higher, and the prevalence of low values was lower in the SQ-LNS group compared with the MMN and IFA groups at 36 wk of gestation ( P  ≤ 0.007). Conclusions: Provision of SQ-LNS containing selenium to pregnant women can be an effective strategy for improving their selenium status. This trial was registered at clinicaltrials.gov (identifier: NCT01239693). Abstract : Provision of small-quantity lipid-based nutrient supplements containing 130 µg/d selenium to pregnant Malawian women for ∼16 wk increased plasma selenium concentrations in late pregnancy.